MILITARY-ENERGY ECOCIDE OF UKRAINE - Kobrzhytskyi, Vsevolod (Collection of scientific papers «ΛΌГOΣ», 2025)
The history of the development of Ukrainian-Russian relations shows that since the times of the national liberation struggle of the Ukrainian people against the Polish oppressors in the middle of the 17th century, the position of the Russian authorities, although it had the appearance of being friendly towards Ukraine and its people, was nevertheless exclusively mercantile and aimed at expanding its own possessions and obtaining political and economic preferences.